ANALISIS KESALAHAN SISWA KELAS VII DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN TEORI NEWMAN DITINJAU DARI ASPEK PROBLEM REPRESENTATION DAN SOLUTION EXECUTION - Mery Puspitasari; Rafiq Zulkarnaen (IKIP Siliwangi, 2021)
Analyze students' mistakes in solving story problems in terms of the aspects of problem representation and solution execution is the aim of this study. Students' mistakes in story problems refer to Newman's theory, including errors: comprehension, transformation, process skills, and encoding. Qualitative descriptive used in this study, with the research subjects were 17 students of class VII at SMPN 3 Tambun Selatan, Bekasi Regency, West Java Province. The test and non-test instruments were used in this study, the test instrument was in the form of story questions related to algebraic form material, while the non-test instrument was an unstructured interview. Research subjects were asked to work on story problems and then analyzed the types of errors. Furthermore, from each type of error, one subject was selected to be interviewed as part of a more in-depth analysis. The results showed that comprehension errors, transformation errors, process skill errors, and encoding errors were caused by errors in the problem representation and solution execution phases. Both phases require students' ability in understanding concepts and fluency in procedures.